Dampak Korupsi terhadap Pertumbuhan Perekonomian Indonesia - Budi, Adi Setya; Lejab, Yuliana Noviyanti B.; Rohi, Wibisono Gunawan; Dima, Enike Tje Yustin (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Corruption is a major obstacle to sustainable economic development in Indonesia. Although the country is rich in natural resources, the persistent corruption across public sectors undermines economic progress. This study aims to examine the impact of corruption on Indonesia’s economic growth by analyzing its effects on investment, productivity, public finance, and service quality. Using a qualitative descriptive approach through a literature review of academic journals, government reports, and institutional data, this research identifies several key implications of corruption on the economy. The findings reveal that corruption reduces both domestic and foreign investment due to legal uncertainty and an uncompetitive business environment. It also leads to inefficient resource allocation in public spending, which in turn decreases national productivity. Furthermore, corruption in taxation systems causes revenue leakage and forces the government to rely heavily on public debt. The study concludes that systemic corruption not only hampers economic growth but also weakens the trust in public institutions, deepens income inequality, and undermines long-term fiscal stability. Addressing corruption is therefore essential to building a transparent, inclusive, and sustainable economic environment in Indonesia.